Continuity of health care for rural diabetic patients and its associates in Sanming city: an interpersonal relationship-based analysis - Shao-yan WU; Yue DAI; Yue-ping LI (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine characteristics and influencing factors of continuity of health care for rural diabetic patients in Sanming city of Fujian province from the perspective of interpersonal relationship for providing references to improve continuous health care for rural diabetic patients. MethodsThe data of 2016 on 2 606 rural diabetic patients in Sanming municipality of Fujian province were extracted from outpatient records registered in New Rural Cooperative Medical System. The interpersonal relationship-related continuity of health care for the diabetic patients was evaluated with following three indicators: usual provider of care (UPC), continuity of care index (COCI), and sequential continuity (SECON). Unconditional multivariate logistic regression analysis was performed to analyze influencing factors of the continuity of health care.ResultsThe interpersonal relationship-related continuity of health care was generally good among the diabetic patients, with the same median value of 1 for UPC, COCI, and SECON. The proportions of the patients with high values of UPC (0.86 - 1), COCI (0.82 - 1), and SECON (0.81 - 1) were 84.80%, 85.61%, and 84.77%; while the proportions of the patients with low values of UPC (0 - 0.85), COCI (0 - 0.81), and SECON (0 - 0.80) were 15.20%, 14.39%, and 15.23%, respectively. The results of unconditional multivariate logistic regression analysis demonstrated that the patients in Shaxian region, visiting a doctor for 5 times or less during the year, without a complication, and seeking medical service mainly in county level or township institutions were more likely to have a high value of both UPC and COCI, while those in Youxi region were more likely to have a low value of both UPC and COCI; the patients being male, visiting a doctor for 5 times or less during the year, without a complication, and seeking medical service mainly in county level or township institutions were more likely to have a high value of SECON but those in Youxi region were more likely to have a low value of SECON.Conclusion The interpersonal relationship-related continuity of health care is generally good and mainly influenced by residential region, yearly frequency of visiting a doctor, situation of complication, and the grade of medical institution frequently being visited for medication among diabetic patients in rural region of Sanming municipality.